PRODUKSI RUANG DI DEPARTEMEN ARSITEKTUR UNDIP: STUDI KUALITATIF PERILAKU MAHASISWA DALAM PEMBENTUKAN RUANG INFORMAL BELAJAR - Bagus Setiono; Agung Budi Sardjono (Tesa Arsitektur, 2026)
At the Department of Architecture, Universitas Diponegoro, students frequently utilize areas outside the classroom—such as corridors and cafeterias—as study spaces in a spontaneous and recurring manner. This research aims to examine the phenomenon of informal space formation by analyzing how student behavior responds to, gives meaning to, and utilizes campus spaces beyond their official functions. Employing a qualitative phenomenological method, data were collected through observations, open-ended questionnaires, and field notes, then analyzed thematically based on the theories of the production of space and environmental behavior. The results indicate that informal spaces are formed through the ways students adapt in search of learning comfort. They select spaces based on the availability of basic amenities (Wi-Fi and power outlets), thermal comfort and natural lighting, easily movable furniture, and proximity to peers for discussions. The novelty of this research highlights that students are not merely passive users, but active agents capable of creating their own study spaces through everyday practices, thereby blurring the boundaries between formal and informal spaces. This study contributes a new perspective for campus designers, suggesting that educational buildings need to provide flexible spaces capable of adapting to the natural habits of their users.